(untitled) - Chaston, Ian (Oxford, 1988)
This book introduces selected aspects of those behavioural skills that are required of individuals if they are to be effective as managers. Each concept in the book is presented in the form of a lively case history of actual situations in fisheries or aquaculture. These are analysed in detail but simplified to highlight specific issues. Practising managers, public sector advisors and students will all find the book full of helpful guidelines and the principles outlined could resolve many real-life problems.
Keywords: Fishing industries,Aquaculture industries; Management,Management